2011
DOI: 10.1021/jm2005089
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent and Selective Inhibitors of Human Platelet-Type 12- Lipoxygenase

Abstract: We report the discovery of novel small molecule inhibitors of platelet type 12-human lipoxygenase, which display nanomolar activity against the purified enzyme, using a quantitative high throughput screen (qHTS) on a library of 153,607 compounds. These compounds also exhibit excellent specificity, >50-fold selectivity vs. the paralogs, 5-human lipoxygenase, reticulocyte 15-human lipoxygenase type-1, and epithelial 15-human lipoxygenase type-2, and >100-fold selectivity vs. ovine cyclooxygenase-1 and human cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 83 publications
0
60
0
2
Order By: Relevance
“…Historically, this field of research has been limited by the lack of selective 12-lipoxygenase inhibitors. We previously reported the discovery, synthesis and optimisation of inhibitors that are highly selective for 12-lipoxygenase [28]. The current proof-of-concept study demonstrates the efficacy of these small-molecule inhibitors of 12-lipoxygenase in protecting rodent and human beta cells from damage associated with inflammation.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Historically, this field of research has been limited by the lack of selective 12-lipoxygenase inhibitors. We previously reported the discovery, synthesis and optimisation of inhibitors that are highly selective for 12-lipoxygenase [28]. The current proof-of-concept study demonstrates the efficacy of these small-molecule inhibitors of 12-lipoxygenase in protecting rodent and human beta cells from damage associated with inflammation.…”
Section: Introductionmentioning
confidence: 79%
“…The identified 8-HQ series exhibited a greater than 100-fold selectivity for inhibition of 12-lipoxygenase relative to other lipoxygenases tested (5-lipoxygenase, 15-lipoxygenase) and COX1 and COX2 [28]. These compounds have made it possible to evaluate 12-lipoxygenase as a mediator of inflammatory cytokine-induced beta cell dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been suggested to play a role in promoting expression of platelet CD62 (P-selectin) [13] and is elevated in patients with essential hypertension [14]. The increasing recognition of the potential importance of 12-HETE in platelet function has led to a recent resurgence of research in the area, which has resulted in the development of novel 12-LOX inhibitors to help elucidate the function of platelet 12-HETE and its potential as a novel anti-platelet target [15,16]. The impact of aspirin on 12-HETE is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…As a typical example, 16) 5,7-dichloro-8-hydroxyquinoline (chloroxine, Chart 1), a topical antimicrobial agent, has been reported to be an inhibitor of biofilm formation of Candida albicans 17) and human platelet type 12-lipoxygenase. 18) It was reported that so-called "caged" drugs, particularly those containing photocleavable protecting groups, play important roles in the control of bioactivities. [19][20][21][22][23][24][25][26] As general (not limited to metal chelators) examples of "caged" biologically active compounds, Hoffman's group reported the design and synthesis of "caged ATP," which is an ATP molecule that is protected by a photocleavable (2-nitro) phenylethyl group, to investigate the function of the Na : K pump in human red blood cells.…”
Section: -Hydroxyquinoline (Hq)-based Compounds Have Recently Been Pmentioning
confidence: 99%